Development and refinement of an online CARD (Comfort Ask Relax Distract) course for organizations and providers delivering vaccinations and other needle procedures - Anna Taddio; Anthony N. T. Ilersich; C. Meghan McMurtry; Kaytlin Constantin; Lucie M. Bucci; Victoria Gudzak; Charlotte Logeman; Natalie Crown; Mandy Kohli; Erin Ledrew; Noni E. MacDonald (Human Vaccines & Immunotherapeutics)
The CARD system (Comfort-Ask-Relax-Distract) is an evidence-based protocol for mitigating vaccine injection-related reactions, such as pain, fear and fainting. We developed a new online CARD training course to educate organizations and providers about CARD and evaluated usability and impact on conceptual knowledge and attitudes. After an initial development phase, three iterative phases of user testing were conducted in individuals with different levels of familiarity with CARD. In the first two phases, experts and non-experts provided feedback using surveys and semi-structured interviews. In the third phase, new learners answered a knowledge test and attitudes survey. Revisions occurred throughout based on qualitative and quantitative analyses, guided by the Universal Design for Learning (UDL) framework. Thirty-one healthcare providers and trainees from 8 disciplines participated across study phases. They held positive attitudes in all components of the UDL, including engagement (e.g. perceptions of relevance and value), representation (e.g. multiple ways included to perceive information, common language), and action and expression (e.g. access to materials, interactivity). Modifications addressed feedback regarding content development, organization and expression of information, and course navigation. Phase 3 participants demonstrated knowledge and positive attitudes about CARD, including confidence and intention to use CARD. In summary, this study developed and refined an online CARD course to educate organizations and providers about CARD in a feasible way and to improve readiness for implementation. The course has the potential to improve efficiency and effectiveness of CARD implementation.